Emotion And Motivation Reflected In Jean Paul Saolome's Female Agent Movie (2010): A Psychoanalytic Criticism - Wijayanti, Rina Ardian, Dr. Phil. Dewi Candrangrum, S.Pd., M.Ed, Drs. Abdillah Nugroho, M. Hum (2013)
The study is to reveal how emotion and motivation major character‟s to be a heroism in the war II for the French and complete their mission in the war II is reflected in Female Agent movie directed by Jean Paul Salome published in 2010. There are two objectives: the first is to analyze the film in term of structural elements and the second is to analyze the film based on Psychoanalytic Criticism. The object of the study is a movie Female Agent movie is directed by Jean Paul Salome. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Female Agent and the secondary data source is journals of emotion and motivation, book of psychoanalytic criticism. The method of collecting data is documentation. The technique of analyzing data is descriptive. The results of the study are as follows. First, based on the structural analysis, Jean Paul Salome as the director of the movie delivers a moral message about the heroism. The structural elements are related to each other and form a solid unity. Second, based on Psychoanalytic criticism, Jean Paul Salome tells emotion and motivation struggled by the major characters.